2008
DOI: 10.1017/s1751731108002619
|View full text |Cite
|
Sign up to set email alerts
|

The effect of footrot on weight gain in sheep

Abstract: Footrot is a highly contagious bacterial disease of sheep affecting the interdigital skin and surrounding soft and hard horn of a hoof, often resulting in severe lameness. This study was aimed at estimating the effect of footrot on weight gain of affected animals, and characterising the variation between animals in terms of phenotypic, environmental and genetic components. A general approach was developed describing the relationship between the disease and weight gain, defining new traits such as the maximum w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…A number of studies have investigated eradication and control strategies (Ennen et al, 2009;Winter, 2009), validation of scoring methods (Conington et al, 2008), and the impact foot rot has on production (Nieuwhof et al, 2008a). This paper presents the development of economic weights for foot rot.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…A number of studies have investigated eradication and control strategies (Ennen et al, 2009;Winter, 2009), validation of scoring methods (Conington et al, 2008), and the impact foot rot has on production (Nieuwhof et al, 2008a). This paper presents the development of economic weights for foot rot.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Considerable research efforts have focused on the investigation of foot-related lameness and its epizootiology, pathogenesis, diagnostic capabilities, and the impact on production, health and welfare status, as well as on the development of effective treatments and application of sustainable preventive measures. The majority of relevant research efforts have focused primarily on cattle [4,5,6,7,8,9,10,11], meat and wool sheep [12,13,14,15], and dairy goats [16,17], highlighting the impact of foot-related lameness on several production traits in these species [12,13,14,15]. Although relevant studies in dairy sheep are limited, recent evidence has suggested a detrimental effect of foot-related lameness on both their well-being and productive efficiency [18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Economic losses from lameness occur in ewes left untreated for one week (Wassink et al, 2010b). Losses arise from ewe deaths and infertility, reduced numbers of lambs born and surviving, and reduced lamb growth rates (Stewart et al, 1984;Marshall et al, 1991;Nieuwhof et al, 2008;Wassink et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%